A MODEL FOR COMMUNITY COLLEGE IN CAMBODIA: Opportunities, Challenges, and Impact on the Relationship with ASEAN - Simon John Crunden; Dr. Paradise Ros (SUJANA: Education and Learning Review, 2025)
Community colleges are extremely important for education in Cambodia. As a result, the community should be more careful and alert to possibilities, difficulties, and their implications for the relationship with ASEAN. This research aims to investigate all elements and topics of the Model for Community College that have an impact on the interactions with ASEAN. We conducted interviews with ten people from various statuses, including teachers, principals, students, policymakers or leaders, and businesspeople/stakeholders. The study included 50 participants from Cambodia's cities and regions, and it used a qualitative technique and convenience sampling. The research findings reveal that stakeholders agree on the potential of Community Colleges in Cambodia to alleviate the education gap and contribute to economic growth. The strategy blends practical skills with academic knowledge to improve graduates' ability to find and potential for future study. The data stresses the role of education in encouraging economic growth, social fairness, poverty reduction, and regional collaboration.